Research on Structural Optimization and Vacuum Performance Improvement of Condenser Air Extraction System of Unit 2 PLTU IPP Sumsel - Wang Zhiliang (Jurnal Syntax Transformation, 2025)
Condenser vacuum level is a crucial parameter affecting the thermal economy of steam turbines and the overall efficiency of the unit. During operation, it was discovered that the condenser air extraction pipeline of Unit 2 at the PLTU IPP Sumsel5 was not installed strictly according to the design drawings, resulting in low extraction efficiency, severe local gas stagnation, and a persistently low vacuum below the design value. To address this, the power plant, taking advantage of the current annual overhaul, conducted a comprehensive study on the treatment and structural optimization of the low condenser vacuum. The air extraction system was redesigned and reinstalled, optimizing 2200 extraction pipelines to achieve efficient airflow distribution and uniform extraction. After the modification, the condenser vacuums stably reached the design value (-93kPa), the turbine back pressure decreased by approximately 3.5kPa, and the unit's thermal efficiency significantly improved, resulting in significant energy savings and operational economic benefits.